2019
DOI: 10.3390/plants8070200
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Silicon Localization and Accumulation in Citrus

Abstract: Several studies have demonstrated Si absorption in monocotyledon and dicotyledon species. Regarding Si accumulation, studies in monocotyledons have identified Si deposition around the cell wall, cuticle layer bulliform cells, silica cells and endodermal cells. In previous studies with different citrus species there were evidence of Si accumulation, however no information on Si deposition can be found. Therefore, in this study, Si was applied (0 and 1000 mg L−1) to the roots of two citrus species, ‘Delta’ Valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…It seems that two main mechanisms of Si absorption coexist in plants, i.e., active and passive, whose relative contributions depend upon both plant species and external Si concentration [ 140 ]. This would explain the strong differences in Si concentration reported within tissues of different plants species [ 141 ]. In any case, Si is taken up by the roots as monosilicic acid with the involvement of channels belonging to the aquaporins’ group, so the water flow resulting from leaf transpiration seems to play a determinant role in defining the rate of Si absorption and transport within the plant [ 142 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…It seems that two main mechanisms of Si absorption coexist in plants, i.e., active and passive, whose relative contributions depend upon both plant species and external Si concentration [ 140 ]. This would explain the strong differences in Si concentration reported within tissues of different plants species [ 141 ]. In any case, Si is taken up by the roots as monosilicic acid with the involvement of channels belonging to the aquaporins’ group, so the water flow resulting from leaf transpiration seems to play a determinant role in defining the rate of Si absorption and transport within the plant [ 142 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…The leaves of mandarin (Citrus reticulata Blanco) trees subjected to Si nutrition for a period of three months demonstrated a significant reduction in the severity of A. alternata infections under controlled conditions in comparison with the control plants [92]. Mvondo-She and Marais [93] reported that a double layer of Si was deposited in the epidermal cell of citrus leaves using electron microscopy (Figure 1). This may explain the enhanced resistance of the citrus plants exposed to Si treatments and show the potential role of Si in providing protection to diseases [21,29].…”
Section: Alternaria Diseasementioning
confidence: 99%
“…This disease control relied upon the regular drenching of potassium silicate in the field [1]. Therefore, it can be inferred that Si protection is not related to the total Si concentration in the root tissue but rather to the availability of mobile silicic acid at the time of infection [93]. A similar study showed that pre-harvest applications of K 2 SiO 3 had the potential to protect citrus fruits ('Delta' Valencia, 'Washington' navel, and Éureka' lemon) from the post-harvest disease P. digitatum, although further research is required to study the biochemical changes induced by silicon application [64,102].…”
Section: Green and Blue Moldmentioning
confidence: 99%
“…Similarly, one can confirm that Y n correctly counts the higher-order descendants of the action of L −1 andL −1 on t ⊗ n t. It is important to note that the above way of producing descendants when acting on multi-particle states cannot be written in terms of the standard Lie-algebraic coproduct ∆(L −1 ) = L −1 ⊗ 1 + 1 ⊗ L −1 (and similarly forL −1 ) acting on t ⊗ t. Simply creating states with powers of the coproduct (∆(L k −1 ) = (∆(L −1 )) k ), as we will do in the next section, would lead to only one state at each level, and would not match B(q,q). The coproduct structure behind this counting will be the subject of an upcoming publication [41].…”
Section: Jhep05(2019)097mentioning
confidence: 99%
“…On the combinatorics side, one could ask what type of coproduct (and associated algebraic structure) would lead to the counting of the Bell polynomial part. This is work in progress [41]. More on the physics side, recall that the Bell polynomial expansion arose from a rewriting of the double-product term in (1.2).…”
Section: Jhep05(2019)097 7 Conclusion and Outlookmentioning
confidence: 99%